Who needs delight? The greater impact of value, trust and satisfaction in utilitarian, frequent-use retail - Loureiro, S. M. C.; Miranda, F.; Breazeale, M. (Journal of Service Management, 2014)
Purpose – The aim of this study is to determine whether the cumulative effects of satisfaction, trust, and perceived value may, under certain conditions, provide more explanatory power for customer loyalty intentions than the often studied and more elusive customer delight. Herzberg's two-factor theory is used to explain why the frequent nature of grocery shopping, a primarily utilitarian experience, might introduce considerations that have not yet been addressed in the study of delight. Design/methodology/approach – A survey is administered to a quota sample of Portuguese supermarket shoppers via phone, using a CATI system. Findings – Research findings suggest that perceived value, trust, and satisfaction have a greater impact on behavioural outcomes than customer delight in the grocery shopping setting. In such a setting, cognitive drivers may be even more important for customers who are primarily concerned with hygiene factors (rather than motivators). Research limitations/implications – Retailers are encouraged to focus on the more mundane factors that influence consumers' perceptions of value and trust rather than trying to invest in the substantial resources required to continually delight consumers. Future research may explore other determinants of loyalty intentions and test the extended model in different service sectors, cultural contexts and countries. Originality/value – This study applies Oliver et al.'s consumer delight model in a utilitarian, frequent-use setting, finding previously undiscovered limitations to its validity.